De Novo Transcriptome Sequencing of the Orange-Fleshed Sweet Potato and Analysis of Differentially Expressed Genes Related to Carotenoid Biosynthesis - Ruijie Li; Hong Zhai; Chen Kang; Degao Liu; Shaozhen He; Qingchang Liu (International Journal of Genomics)
Sweet potato, Ipomoea batatas (L.) Lam., is an important food crop worldwide. The orange-fleshed sweet potato is considered to be an important source of beta-carotene. In this study, the transcriptome profiles of an orange-fleshed sweet potato cultivar “Weiduoli” and its mutant “HVB-3” with high carotenoid content were determined by using the high-throughput sequencing technology. A total of 13,767,387 and 9,837,090 high-quality reads were produced from Weiduoli and HVB-3, respectively. These reads were de novo assembled into 58,277 transcripts and 35,909 unigenes with an average length of 596 bp and 533 bp, respectively. In all, 874 differentially expressed genes (DEGs) were obtained between Weiduoli and HVB-3, 401 of which were upregulated and 473 were downregulated in HVB-3 compared to Weiduoli. Of the 697 DEGs annotated, 316 DEGs had GO terms and 62 DEGs were mapped onto 50 pathways. The 22 DEGs and 31 transcription factors involved in carotenoid biosynthesis were identified between Weiduoli and HVB-3. In addition, 1,725 SSR markers were detected. This study provides the genomic resources for discovering the genes involved in carotenoid biosynthesis of sweet potato and other plants.